Adhesive agent composition, adhesive agent film for circuit connection, circuit connection structure, and method for manufacturing the same

A non-conductive filler with low thermal expansion is integrated into an adhesive composition to enhance the reliability of circuit connections by reducing interfacial peeling, ensuring stable resistance under high-temperature and high-humidity conditions.

JP2025009381APending Publication Date: 2025-01-20RESONAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023112356
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing circuit connection structures face challenges in maintaining high-temperature and high-humidity connection reliability due to interfacial peeling at the interface between conductive particles and electrodes, especially when non-conductive fillers are added to improve reliability, leading to increased connection resistance.

Method used

Incorporation of a non-conductive filler with an average coefficient of linear thermal expansion of 0 ppb/°C between 30°C and 150°C, along with a thermosetting component, conductive particles, and a radically polymerizable compound, to form an adhesive composition that reduces interfacial peeling and maintains reliable connections under harsh conditions.

Benefits of technology

The solution provides a circuit connection structure with excellent high-temperature and high-humidity reliability by minimizing interfacial peeling and maintaining stable connection resistance, even under severe environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009381000003
    Figure 2025009381000003
  • Figure 2025009381000001
    Figure 2025009381000001
  • Figure 2025009381000002
    Figure 2025009381000002
Patent Text Reader

Abstract

To provide an adhesive agent film for circuit connection that can yield a circuit connection structure with excellent connection reliability under high temperature and high humidity conditions.SOLUTION: This adhesive agent film for circuit connection contains a thermoplastic resin, a thermosetting component, conductive particles, and a non-conductive filler. The non-conductive filler includes a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less from 30°C to 150°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition, an adhesive film for circuit connection, a circuit connection structure, and a method for producing the same. [Background technology]

[0002] Thermosetting resins using epoxy resins that are highly adhesive and highly reliable are known as circuit connecting materials for semiconductor elements and liquid crystal display elements (see, for example, Patent Document 1). The resin components generally used are epoxy resins, curing agents such as phenolic resins that are reactive with epoxy resins, and latent curing agents that promote the reaction between the epoxy resin and the curing agent. The latent curing agent is an important factor that determines the curing temperature and curing speed, and various compounds are used from the viewpoints of storage stability at room temperature and curing speed when heated.

[0003] Recently, radical curing adhesives that use acrylate derivatives and / or methacrylate derivatives (hereinafter collectively referred to as "(meth)acrylate derivatives") in combination with peroxides, which are radical polymerization initiators, have been attracting attention. Radical curing allows for short-term curing because radicals, which are reactive species, are highly reactive (see, for example, Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-113480 [Patent Document 2] JP 2002-203427 A [Patent Document 3] International Publication No. 98 / 044067 Brochure Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, an adhesive film having anisotropic conductivity in which conductive particles are dispersed in the adhesive is used to connect circuit members. A circuit connection structure manufactured using such an adhesive film has a connection part formed in which opposing electrodes are electrically connected via the conductive particles. The connection part contains a cured product of the adhesive containing the thermosetting component as described above, which fixes the conductive particles and the electrodes.

[0006] Although the conductive particles can improve the conductivity between electrodes in a circuit connection structure, the circuit connection structure is also required to have a property that the connection resistance between opposing electrodes is not likely to increase even under high temperature and high humidity conditions (hereinafter, also referred to as "high temperature and high humidity connection reliability"). In addition, in fields such as circuits for liquid crystal display elements, circuits are becoming increasingly narrower, and mounting at lower temperatures and in shorter times is required to reduce thermal damage to the circuits. Under such mounting conditions, the reactivity of the adhesive film decreases, making it difficult to obtain high temperature and high humidity connection reliability.

[0007] Therefore, an object of the present invention is to provide an adhesive composition and an adhesive film for circuit connection that can provide a circuit connection structure having excellent high-temperature and high-humidity connection reliability, as well as a circuit connection structure having excellent high-temperature and high-humidity connection reliability and a method for producing the same. [Means for solving the problem]

[0008] The present inventors have found that peeling may occur at the interface between the circuit member and the cured resin by observing the connection of the circuit connection structure after high temperature and high humidity testing. If the interface peeling occurs around the contact point between the conductive particles and the electrode, the contact area may decrease and the connection resistance may increase. Furthermore, according to the study by the present inventors, it has become clear that such interface peeling is likely to become evident when a non-conductive filler is highly blended in order to improve the high temperature and high humidity connection reliability. Therefore, as a result of further intensive study, the present inventors have found that by blending a specific non-conductive filler, the area of ​​the above-mentioned interface peeling can be reduced even after a severe high temperature and high humidity test, and have completed the present invention.

[0009] The gist of the present invention is the following [1] to [9].

[0010] [1] An adhesive composition comprising a thermosetting component, conductive particles, and a non-conductive filler, the non-conductive filler comprising a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less over the temperature range from 30°C to 150°C. [2] The adhesive composition according to [1], wherein the content of the non-conductive filler MF is 0.1 to 50 mass % based on the total mass of the adhesive composition excluding the conductive particles and the non-conductive filler. [3] The adhesive composition according to [1] or [2], comprising, as the thermosetting component, a radical polymerizable compound and a radical polymerization initiator. [4] The adhesive composition according to any one of [1] to [3], further comprising a thermoplastic resin. [5] The adhesive composition according to any one of [1] to [4], which has a reaction rate of 90% or more when heated at 180°C for 1 minute. [6] An adhesive film for circuit connection comprising a thermoplastic resin, a thermosetting component, conductive particles, and a non-conductive filler, the non-conductive filler including a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less over the temperature range from 30°C to 150°C. [7] The adhesive film for circuit connection described in [6], wherein the content of the non-conductive filler MF is 0.1 to 50 mass % based on the total mass of the adhesive film excluding the conductive particles and the non-conductive filler. [8] The adhesive film for circuit connection according to [6] or [7], comprising as the thermosetting component a radically polymerizable compound and a radical polymerization initiator. [9] The adhesive film for circuit connection according to any one of [6] to [8], which has a reaction rate of 90% or more when heated at 180°C for 1 minute.

[10] A circuit connection structure comprising: a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, the connection portion including conductive particles and a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less between 30°C and 150°C.

[11] The circuit connection structure according to

[10] , wherein the connection portion comprises a cured product of the adhesive composition according to any one of [1] to [5].

[12] A method for producing a circuit connection structure, comprising a step of heating and pressurizing a first circuit member having a first electrode, a second circuit member having a second electrode, and an adhesive film for circuit connection described in any of [6] to [8] while the first electrode and the second electrode are arranged opposite each other via the adhesive film for circuit connection, to electrically connect the first electrode and the second electrode. Effect of the Invention

[0011] According to the present invention, it is possible to provide an adhesive composition and an adhesive film for circuit connection which can provide a circuit connection structure having excellent high-temperature and high-humidity connection reliability, as well as a circuit connection structure having excellent high-temperature and high-humidity connection reliability and a method for producing the same. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a connection structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain stage of the numerical range may be replaced with the upper limit or lower limit of the numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In addition, the upper limit and lower limit values ​​described individually can be arbitrarily combined. In this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl". In addition, "(poly)" means both the case with and without the prefix "poly". In addition, "A or B" may include either A or B, or may include both. In addition, the materials exemplified below may be used alone or in combination of two or more types, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.

[0014] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings where necessary. However, the present invention is not limited to the following embodiments.

[0015] <Adhesive composition> The adhesive composition of the present embodiment contains a thermosetting component, conductive particles, and a non-conductive filler.

[0016] As the thermosetting component, a combination of a radical polymerizable compound and a radical polymerization initiator, or an epoxy resin and a curing agent, etc. can be used.

[0017] In the present embodiment, from the viewpoints of shortening production time and ease of handling, (A) a thermoplastic resin (hereinafter also referred to as "component (A)"), (B) a radical polymerizable compound (hereinafter also referred to as "component (B)"), and (C) a radical polymerization initiator (hereinafter also referred to as "component (C)") may be contained.

[0018] [Component (A): Thermoplastic resin] As the component (A), polyvinyl butyral resin, polyvinyl formal resin, polyamide resin, polyester resin, phenol resin, epoxy resin, phenoxy resin, polystyrene resin, xylene resin, polyurethane resin, polyester urethane resin, etc. These can be used alone or in combination of two or more.

[0019] The weight-average molecular weight of the above thermoplastic resin is set to 1.0×10 from the viewpoint of film-forming properties. 4 or more, and from the viewpoint of mixing, 1.0×10 4 Above 1.0×10 6 It may be less than.

[0020] The weight average molecular weight of a thermoplastic resin is measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. [GPC conditions] Equipment used: Hitachi L-6000 type [Hitachi, Ltd.], Column: Gelpack GL-R420 + Gelpack GL-R430 + Gelpack GL-R440 (total of 3) [Hitachi Chemical Co., Ltd.], Eluent: Tetrahydrofuran, Measurement temperature: 40°C, Flow rate: 1.75 ml / min, Detector: L-3300RI [Hitachi, Ltd.]

[0021] The component (A) has a glass transition temperature (Tg) of 40° C. or higher and a weight average molecular weight of 1.0×10 4 The above-mentioned hydroxyl-containing resin (for example, phenoxy resin) can be used. The hydroxyl-containing resin may be modified with an epoxy-containing elastomer.

[0022] In this specification, the thermoplastic resin having a radically polymerizable functional group is blended as the radically polymerizable compound (B).

[0023] The phenoxy resin can be obtained by reacting a difunctional phenol with an epihalohydrin to a high molecular weight, or by subjecting a difunctional epoxy resin to a polyaddition reaction with a difunctional phenol. Furthermore, a polyester urethane resin may be used as the component (A).

[0024] From the viewpoint of further improving the peel-suppressing effect, the content of component (A) in the adhesive composition may be 5 mass % or more or 30 mass % or more, and may be 80 mass % or less or 60 mass % or less, or may be 5 to 80 mass % or 30 to 60 mass %, based on the resin components of the adhesive composition (e.g., components other than the conductive particles and the non-conductive filler).

[0025] [Component (B): radically polymerizable compound] As the (B) component, a compound having a radical polymerizable functional group can be used. Examples of the radical polymerizable functional group include a vinyl group, an acryloyl group, and a methacryloyl group. Among these, a compound having an acryloyl group and / or a methacryloyl group is more preferable. As the (B) component, one type can be used alone or two or more types can be used in combination.

[0026] The adhesive composition of this embodiment may also use, as component (B), polymers such as polyurethane, polystyrene, polyethylene, polyvinyl butyral, polyvinyl formal, polyimide, polyamide, polyester, polyvinyl chloride, polyphenylene oxide, urea resin, melamine resin, phenol resin, xylene resin, epoxy resin, polyisocyanate resin, and phenoxy resin. The polymer used as component (B) has at least one radically polymerizable functional group in the molecule.

[0027] Inclusion of a polymer as component (B) is preferred since it provides good handling properties and excellent stress relaxation during curing, and it is even more preferred if the polymer has a functional group such as a hydroxyl group since this improves adhesiveness.

[0028] The weight average molecular weight of the above polymer is 1.0×10 4 or more, and from the viewpoint of mixing, 1.0×10 4 Above 1.0×10 6 The weight average molecular weight here is measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the conditions described in the Examples.

[0029] As the component (B), from the viewpoint of improving connection reliability under high temperature and high humidity conditions, a (poly)urethane (meth)acrylate compound can be used.

[0030] From the viewpoint of the balance between crosslink density and cure shrinkage, the content of the (poly)urethane (meth)acrylate compound may be 40 to 95 mass %, 50 to 90 mass %, or 55 to 85 mass % based on the total mass of the component (B).

[0031] Examples of the (B) component that can be used include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, 2-hydroxy-1,3-di(meth)acryloxypropane, 2,2-bis[4-((meth)acryloxymethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloxypolyethoxy)phenyl]propane, dicyclopentenyl (meth)acrylate, tricyclodecanyl (meth)acrylate, tris((meth)acryloyloxyethyl)isocyanurate, urethane (meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, isocyanuric acid EO (ethylene oxide) modified diacrylate, and 2-methacryloyloxyethyl acid phosphate.

[0032] The component (B) can be one having at least one partial structure selected from the group consisting of a dicyclopentane skeleton, a tricyclodecane skeleton, and a triazine ring.

[0033] From the viewpoint of balancing the crosslink density and cure shrinkage and further reducing the connection resistance, the (B) component may contain a (meth)acrylate compound having a tricyclodecane skeleton. From the viewpoint of balancing the crosslink density and cure shrinkage, the content of the (meth)acrylate compound having a tricyclodecane skeleton may be, for example, 0 to 90 mass%, 5 to 60 mass%, or 10 to 30 mass% based on the total mass of the (B) component.

[0034] The component (B) may contain a (meth)acrylate compound (a (meth)acrylate compound having a phosphate ester structure) represented by the following formula (1). In this case, the adhesive strength to the surface of an inorganic material (metal, etc.) is improved, making it suitable for bonding electrodes (for example, circuit electrodes). [ka] In formula (1), n ​​represents an integer of 1 to 3, and R represents a hydrogen atom or a methyl group.

[0035] The (meth)acrylate compound represented by formula (1) can be obtained, for example, by reacting phosphoric anhydride with 2-hydroxyethyl (meth)acrylate. Specific examples of the (meth)acrylate compound represented by formula (1) include mono(2-(meth)acryloyloxyethyl) acid phosphate, di(2-(meth)acryloyloxyethyl) acid phosphate, etc.

[0036] The content of the (meth)acrylate compound represented by formula (1) may be, for example, 1 to 10 mass %, 2 to 5 mass %, or 2.5 to 4 mass % based on the total mass of the (B) component, in that it is easier to obtain a crosslink density required for reducing connection resistance and improving connection reliability.

[0037] The content of component (B) in the adhesive film for circuit connection may be 5 mass % or more, 20 mass % or more, or 40 mass % or more, based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and the non-conductive filler), from the viewpoint of reducing connection resistance and making it easier to obtain the crosslink density required to improve high-temperature and high-humidity resistant connection reliability, and may be 90 mass % or less, 75 mass % or less, or 60 mass % or less, or may be 5 to 90 mass %, 20 to 75 mass %, or 40 to 60 mass %.

[0038] [Component (C): Radical polymerization initiator] As the component (C), a compound that generates free radicals can be used, such as a peroxide compound or an azo compound that decomposes when heated to generate free radicals. The radical polymerization initiator is appropriately selected depending on the intended connection temperature, connection time, etc. As the component (C), one type can be used alone, or two or more types can be used in combination.

[0039] Examples of the radical polymerization initiator include diacyl peroxides, peroxydicarbonates, peroxy esters, peroxy ketals, dialkyl peroxides, and hydroperoxides.

[0040] Examples of diacyl peroxides include 2,4-dichlorobenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, succinic peroxide, benzoylperoxytoluene, and benzoyl peroxide.

[0041] Examples of peroxydicarbonates include di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, di-2-ethoxymethoxyperoxydicarbonate, di(2-ethylhexylperoxy)dicarbonate, dimethoxybutylperoxydicarbonate, and di(3-methyl-3-methoxybutylperoxy)dicarbonate.

[0042] Peroxy esters include 1,1,3,3-tetramethylbutyl peroxy neodecanoate, 1-cyclohexyl-1-methylethyl peroxy neodecanoate, t-hexyl peroxy neodecanoate, t-butyl peroxy pivalate, 1,1,3,3-tetramethylbutyl peroxy 2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, 1-cyclohexyl-1-methylethyl peroxy 2-ethylhexanoate, t-hexyl peroxy 2-ethylhexanoate, and t-butyl peroxy pivalate. Examples of the peroxyalkylene oxide include 2-ethylhexanoate, t-butylperoxyisobutyrate, 1,1-bis(t-butylperoxy)cyclohexane, t-hexylperoxyisopropyl monocarbonate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5-dimethyl-2,5-di(m-toluoylperoxy)hexane, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexylperoxybenzoate, and t-butylperoxyacetate.

[0043] Examples of peroxyketals include 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-(t-butylperoxy)cyclododecane, and 2,2-bis(t-butylperoxy)decane.

[0044] Examples of dialkyl peroxides include α,α'-bis(t-butylperoxy)diisopropylbenzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and t-butylcumyl peroxide.

[0045] Examples of the hydroperoxides include diisopropylbenzene hydroperoxide and cumene hydroperoxide.

[0046] These radical polymerization initiators may be used in combination with a decomposition accelerator, inhibitor, etc. Furthermore, it is preferable to microencapsulate these radical polymerization initiators by coating them with a polyurethane or polyester polymeric substance, etc., in order to extend the shelf life.

[0047] From the viewpoint of pot life, the content of component (C) in the adhesive composition may be 0.1 mass % or more, 0.5 mass % or more, or 1 mass % or more, and may be 20 mass % or less, 10 mass % or less, or 5 mass % or less, or may be 0.1 to 20 mass %, 0.5 to 10 mass %, or 1 to 5 mass %, based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and the non-conductive filler).

[0048] [Conductive particles] The conductive particles may be metal particles such as Au, Ag, Ni, Cu, solder, conductive carbon particles made of conductive carbon, etc. The conductive particles may be those in which the surface of transition metals such as Ni is coated with precious metals such as Au. From the viewpoint of obtaining a sufficient pot life, the surface layer may be Au, Ag, platinum group precious metals, or Au. The conductive particles may be coated conductive particles in which a conductive layer is formed on the surface of non-conductive particles such as glass, ceramic, plastic, etc. by a method such as coating the surface of the non-conductive particles with the above-mentioned conductive material, and the outermost layer is further composed of precious metals. When such particles or heat-melting metal particles are used, they have deformability by heating and pressing, so that the contact area with the electrode increases during connection, and reliability can be improved.

[0049] The conductive particles may be insulating coated conductive particles comprising the above-mentioned metal particles, conductive carbon particles, or coated conductive particles, and an insulating layer containing an insulating material such as resin and coating the surfaces of the particles. When the conductive particles are insulating coated conductive particles, even if the content of the conductive particles is high, the surfaces of the particles are coated with resin, so that the occurrence of short circuits due to contact between the conductive particles can be suppressed, and the insulation between adjacent electrode circuits can also be improved.

[0050] The conductive particles may be one type of the above-mentioned various conductive particles used alone or two or more types may be used in combination.

[0051] The maximum particle size of the conductive particles must be smaller than the minimum interval between the electrodes (the shortest distance between adjacent electrodes). From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles may be 50 μm or less, 30 μm or less, or 20 μm or less. From these viewpoints, the maximum particle size of the conductive particles may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm. In this specification, the particle size of 300 arbitrary conductive particles (pcs) is measured by observation using a scanning electron microscope (SEM), and the largest value obtained is defined as the maximum particle size of the conductive particles. In addition, when the conductive particles are not spherical, such as having protrusions, the particle size of the conductive particles is defined as the diameter of a circle circumscribing the conductive particles in an SEM image.

[0052] The average particle size of the conductive particles may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more, from the viewpoint of excellent dispersibility and conductivity. The average particle size of the conductive particles may be 50 μm or less, 30 μm or less, or 20 μm or less, from the viewpoint of excellent dispersibility and conductivity. From these viewpoints, the average particle size of the conductive particles may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm. In this specification, the particle size of any 300 conductive particles (pcs) is measured by observation using a scanning electron microscope (SEM), and the average value of the particle sizes obtained is defined as the average particle size.

[0053] The content of the conductive particles in the adhesive composition may be in the range of 0.1 to 30 parts by volume relative to 100 parts by volume of the resin components of the adhesive composition (e.g., components other than the conductive particles and the non-conductive filler) in order to facilitate obtaining a stable connection resistance. The content of the conductive particles may be 0.1 to 10 parts by volume in order to prevent short circuits between adjacent circuits caused by excess conductive particles.

[0054] Furthermore, the content of the conductive particles may be 0.5 to 60 mass%, 3 to 45 mass%, or 6 to 30 mass%, based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and the non-conductive filler), in that stable connection resistance is easily obtained.

[0055] [Non-conductive filler] The adhesive composition of the present embodiment contains, as a non-conductive filler, a non-conductive filler MF (hereinafter also referred to as "(MF) component") having an average linear thermal expansion coefficient of 0 ppb / °C or less over the temperature range from 30°C to 150°C.

[0056] The adhesive composition of the present embodiment contains the (MF) component, which allows a circuit connection structure with excellent connection reliability under high temperature and high humidity conditions to be obtained. The inventors speculate that this effect is achieved by the (MF) component being able to alleviate both the outward stress caused by the expansion of the cured product of the adhesive composition constituting the connection part upon heating, and the inward stress caused by the contraction of the cured product after heating.

[0057] The average linear thermal expansion coefficient of the filler between 30° C. and 150° C. can be measured, for example, by a thermal dilatometer that detects the elongation of a sample using a laser interferometer, an X-ray diffraction method, or the like.

[0058] The (MF) component may be an inorganic filler or a spherical inorganic filler from the viewpoints of lowering the melt viscosity, further reducing the connection resistance, and improving the high-temperature and high-humidity connection reliability.

[0059] Examples of inorganic fillers include glass fillers, zirconium phosphate-based fillers, cordierite-based fillers, silicon oxide-based fillers, zirconium tungstate-based fillers, and manganese nitride-based fillers. Among these, from the viewpoint of lowering the melt viscosity, further reducing the connection resistance, and improving the high-temperature and high-humidity connection reliability, one or more types selected from glass fillers and zirconium phosphate-based fillers can be used. The glass filler may be a titanium-doped glass filler or a titanium-doped spherical glass filler.

[0060] The (MF) component may be a commercially available product, such as "DL7400" (manufactured by Nippon Electric Glass Co., Ltd., trade name, linear thermal expansion coefficient (average value from 30 to 150°C): -1.1 ppm / °C), "AZ Filler" (manufactured by Asahi Glass Co., Ltd., trade name, linear thermal expansion coefficient (average value from 30 to 150°C): 0.2 ppm / °C), or "ZWP" (manufactured by Kyoritsu Material Co., Ltd., trade name, linear thermal expansion coefficient (average value from 30 to 150°C): -0.3 ppm / °C).

[0061] The average particle size (primary particle size) of the (MF) component may be 5 nm to 5 μm, 1 μm to 5 μm, 5 nm to 2 μm, 10 nm to 100 nm, or 10 nm to 30 nm, from the viewpoints of increasing the contact area between the conductive particles and the electrode, further reducing the connection resistance, and improving the high-temperature and high-humidity connection reliability.

[0062] The specific gravity of the (MF) component is 1 g / cm from the viewpoints of preventing separation of the varnish and ensuring uniformity of the composition within the film. 3 ~7g / cm 3 1 g / cm 3 ~5g / cm 3 1.5 g / cm 3 ~3g / cm 3 may be also possible.

[0063] The content of the (MF) component may be 0.1 to 50 mass %, or may be 5 to 25 mass %, based on the total mass of the adhesive composition (resin component) excluding the conductive particles and the non-conductive filler.

[0064] The content of the (MF) component, based on the total amount of non-conductive filler contained in the adhesive composition, may be 1 mass % or more, 50 mass % or more, 75 mass % or more, 90 mass % or more, or may be 100 mass %.

[0065] The adhesive composition of the present embodiment may contain a non-conductive filler other than the (MF) component. The other non-conductive filler may be either an inorganic filler or an organic filler. Examples of the inorganic filler include inorganic fine particles such as metal oxide fine particles, such as silica fine particles, alumina fine particles, silica-alumina fine particles, titania fine particles, and zirconia fine particles; and nitride fine particles. Examples of the organic filler include organic fine particles, such as silicone fine particles, methacrylate-butadiene-styrene fine particles, acrylic-silicone fine particles, polyamide fine particles, and polyimide fine particles.

[0066] The adhesive composition of the present embodiment may further contain other components in addition to the above-mentioned components. Examples of the other components include a thiol compound (hereinafter also referred to as component (D)), a coupling agent (hereinafter also referred to as component (E)), etc. These components may be used alone or in combination of two or more.

[0067] The thiol compound which is the component (D) may be a thiol compound having one thiol group (monofunctional thiol compound), or a thiol compound having multiple thiol groups (polyfunctional thiol compound).

[0068] The thiol group contained in the component (D) may be a primary thiol group, a secondary thiol group, or a tertiary thiol group.

[0069] Examples of monofunctional thiol compounds include 2-mercaptobenzothiazole, 2-methyl-4,5-dihydrofuran-3-thiol, 3-mercapto-1-hexanol, mercaptomethylbutanol, 3-mercapto-2-methylpentanol, 3-mercapto-3-methylbutanol, 4-ethoxy-2-methyl-2-butanethiol, hexanethiol, isobutylthiol, 1,1-dimethylheptanethiol, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.

[0070] Examples of polyfunctional thiol compounds include pentaerythritol tetrakis(3-mercaptobutyrate), ethanedithiol, 1,3-propanethiol, 1,4-butanethiol, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, and tetraethylene glycol bis(3-mercaptopropionate).

[0071] The content of the (D) component may be 0.05 mass% or more, 0.5 mass% or more, 1.0 mass% or more, or 1.5 mass% or more based on the total mass of the resin components of the adhesive composition (e.g., components other than conductive particles and non-conductive fillers) from the viewpoint of suppressing peeling at the interface between the adhesive composition and the circuit member after curing and suppressing an increase in the connection resistance of the circuit connection structure. Also, the content of the (D) component may be 5.0 mass% or less, 3.0 mass% or less, 2.5 mass% or less, or 2.0 mass% or less based on the total mass of the resin components of the adhesive composition (e.g., components other than conductive particles and non-conductive fillers) from the viewpoint of suppressing peeling at the interface between the adhesive composition and the circuit member after curing and suppressing an increase in the connection resistance of the circuit connection structure.

[0072] As the coupling agent, which is the component (E), a compound having at least one of a vinyl group, an acrylic group (acryloyl group), an amino group, an epoxy group, or an isocyanate group can be used from the viewpoint of improving adhesiveness. The coupling agent may be a silane coupling agent, and examples thereof include vinyltrimethoxysilane, vinyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, and condensates thereof.These may be used alone or in combination of two or more.

[0073] The content of component (E) may be 0.5 mass % or more, 1 mass % or more, or 2 mass % or more, and may be 15 mass % or less, 10 mass % or less, or 5 mass % or less, based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and the non-conductive filler).

[0074] Furthermore, the adhesive composition of the present embodiment may contain other additives such as a softener, an accelerator, an antiaging agent, a colorant, a flame retardant, a thixotropic agent, a polymerization inhibitor, etc. Examples of the polymerization inhibitor include hydroquinone and methyl ether hydroquinones.

[0075] The adhesive composition of the present embodiment may have a reaction rate of 80% or more, or may have a reaction rate of 90% or more when heated for 1 minute at 180° C. The reaction rate is determined by the following procedure. (Response rate) Two pre-heated samples each containing 5 mg of the adhesive composition are prepared. Next, one pre-heated sample is heated in an air atmosphere (atmosphere) at 180°C for 1 minute to obtain a post-heated sample. For each of the pre-heated sample and the post-heated sample, a differential scanning calorimetry (DSC) device (product name DSC7, manufactured by PERKIN ELMER) is used to measure the DSC calorific value under a nitrogen gas flow at a measurement temperature range of 30°C to 250°C and a heating rate of 10°C / min. Based on the measured DSC calorific value, the reaction rate when heated at 180°C for 1 minute is calculated using the following formula. Reaction rate = (Cx-Cy) x 100 / Cx [In the formula, Cx represents the DSC calorific value (J / g) of the sample before heating, and Cy represents the DSC calorific value (J / g) of the sample after heating.]

[0076] <Adhesive film for circuit connection> The adhesive film for circuit connection of this embodiment can contain a thermoplastic resin, a thermosetting component, conductive particles, and a non-conductive filler, and can have a configuration similar to that of the adhesive composition of this embodiment described above.

[0077] With regard to the content of each component, "based on the total amount of the adhesive composition" shall be read as "based on the total amount of the adhesive film," and "based on the total mass of the resin components of the adhesive composition (e.g., components other than conductive particles and non-conductive fillers)" shall be read as "based on the total mass of the resin components of the adhesive film (e.g., components other than conductive particles and non-conductive fillers)."

[0078] The adhesive film for circuit connection of this embodiment may have a reaction rate of 80% or more, or may have a reaction rate of 90% or more, when heated for 1 minute at 180° C. The reaction rate is determined in the same manner as above, except that two samples of 5 mg of the adhesive film are prepared as pre-heated samples.

[0079] The particle density of the conductive particles in the circuit connecting adhesive film is set to 100 particles / mm from the viewpoint of obtaining a stable connection resistance. 2 More than 1000 pieces / mm 2 or more than 3000 pieces / mm 2 From the viewpoint of ensuring the insulation between adjacent electrodes, the particle density of the conductive particles in the adhesive film for circuit connection may be 100,000 particles / mm 2 Below, 50000 pieces / mm 2 or less than 30,000 pieces / mm 2 From these viewpoints, the particle density of the conductive particles in the adhesive film for circuit connection may be 100 to 100,000 particles / mm 2 , 1000~50000 pieces / mm 2 , or 3000 to 30000 pieces / mm 2 It may be.

[0080] The thickness of the adhesive film for circuit connection may be, for example, 3 μm or more, or 10 μm or more, and may be 50 μm or less, 30 μm or less, or 20 μm or less.

[0081] The adhesive film for circuit connection of this embodiment can be suitably used as an adhesive film for circuit connection for connecting a first circuit member having a first electrode (e.g., a first circuit member having a first circuit electrode formed on the main surface of a first substrate) and a second circuit member having a second electrode (e.g., a second circuit member having a second circuit electrode formed on the main surface of a second substrate) with the first electrode and the second electrode (the first circuit electrode and the second circuit electrode) arranged opposite each other.

[0082] The adhesive film for circuit connection may have a multi-layer structure of two or more layers, since this makes it easier to obtain a stable connection resistance.

[0083] The circuit connection adhesive film of this embodiment can be produced by the following method. Specifically, first, the (A) component, the thermosetting component (e.g., the (B) component and the (C) component), the conductive particles, the non-conductive filler MF, and other components added as necessary are added to a solvent (organic solvent), and dissolved or dispersed by stirring, mixing, kneading, etc. to prepare a varnish composition (varnish-like adhesive composition). Thereafter, the varnish composition is applied to a release-treated substrate using a knife coater, roll coater, applicator, comma coater, die coater, etc., and the solvent is volatilized by heating to form a circuit connection adhesive film on the substrate.

[0084] The solvent used in preparing the varnish composition may be a solvent that has the property of dissolving or dispersing each component uniformly. Examples of such solvents include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, and butyl acetate. These solvents can be used alone or in combination of two or more. The stirring and mixing and kneading in preparing the varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, or a homodisper.

[0085] The substrate is not particularly limited as long as it has heat resistance sufficient to withstand the heating conditions for volatilizing the solvent. For example, substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. can be used.

[0086] The heating conditions for volatilizing the solvent from the varnish composition applied to the substrate may be conditions that allow the solvent to volatilize sufficiently, for example, at 40° C. or higher and 120° C. or lower for 0.1 minutes or longer and 10 minutes or shorter.

[0087] In the adhesive film for circuit connection of this embodiment, a part of the solvent may remain unremoved. The content of the solvent in the adhesive film for circuit connection of this embodiment may be, for example, 10 mass % or less, or 5 mass % or less, based on the total mass of the adhesive film.

[0088] <Circuit connection structure and method for producing same> Next, the circuit connection structure and the method for producing the same will be described.

[0089] The circuit connection structure of the present embodiment comprises a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, the connection portion containing conductive particles and a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less between 30°C and 150°C. The connection portion may contain the adhesive composition of the present embodiment or a cured product of the adhesive film for circuit connection of the present embodiment.

[0090] The method for manufacturing the circuit connection structure of this embodiment includes a step of heating and pressurizing a first circuit member having a first electrode, a second circuit member having a second electrode, and the adhesive film for circuit connection of this embodiment while the first electrode and the second electrode are arranged facing each other with the adhesive film for circuit connection interposed therebetween, thereby electrically connecting the first electrode and the second electrode.

[0091] Fig. 1 is a schematic cross-sectional view showing one embodiment of a circuit connection structure. The circuit connection structure 1 shown in Fig. 1 includes a first circuit member 20 having a first circuit board 21 and a first circuit electrode (first connection terminal) 22 formed on a main surface 21a of the first circuit board 21, a second circuit member 30 having a second circuit electrode (second connection terminal) 32 formed on a main surface 31a of the second circuit board 31, and a connection portion 10 interposed between the first circuit member 20 and the second circuit member 30 to bond them together. The second circuit member 30 is disposed opposite the first circuit member 20 such that the second circuit electrode 32 faces the first circuit electrode 22.

[0092] The connection part 10 is formed by interposing the circuit connection adhesive film of this embodiment between the first circuit member 20 and the second circuit member 30 and applying pressure in this state, and includes a cured product of the circuit connection adhesive film. Note that this embodiment shows an example of a case where the connection part 10 is formed using a circuit connection adhesive film containing conductive particles, and the connection part 10 is composed of an insulating layer 11 and conductive particles 7 dispersed in the insulating layer 11. The insulating layer 11 is derived from a component of the adhesive film other than the conductive particles, and can include, for example, a cured product formed by radical polymerization of a radically polymerizable compound.

[0093] The opposing first circuit electrodes 22 and second circuit electrodes 32 are electrically connected via conductive particles 7. On the other hand, the first circuit electrodes 22 and the second circuit electrodes 32 formed on the same circuit board are insulated from each other.

[0094] Examples of the first circuit board 21 and the second circuit board 31 include chip components such as semiconductor chips, resistor chips, and capacitor chips, and substrates such as printed circuit boards. Usually, a circuit member is provided with multiple connection terminals, but in some cases, the number of connection terminals may be single.

[0095] More specifically, a substrate made of an inorganic material such as a semiconductor, glass, or ceramic, a plastic substrate, or a glass / epoxy substrate is used. Examples of the plastic substrate include a polyimide film, a polycarbonate film, and a polyester film. The first circuit electrode and the second circuit electrode are formed of a metal such as copper. In order to obtain a better electrical connection, it is preferable that the surface of at least one of the first circuit electrode and the second circuit electrode is made of a metal selected from gold, silver, tin, and the platinum group. The surface layer is selected from any of gold, silver, the platinum group, and tin, and these may be used in combination. In addition, a multi-layer structure may be formed by combining multiple metals such as copper / nickel / gold.

[0096] Alternatively, one of the first circuit member 20 and the second circuit member 30 may be a liquid crystal display panel having a glass substrate or a plastic substrate as a circuit board and having a connection terminal formed from ITO or the like. Alternatively, one of the first circuit member 20 and the second circuit member 30 may be a flexible printed circuit board (FPC) having a polyimide film as a circuit board, a tape carrier package (TCP) or a chip-on-film (COF), or a semiconductor silicon chip having a semiconductor substrate as a circuit board. The circuit connection structure is constructed by appropriately combining these various circuit members as necessary.

[0097] In order to eliminate the influence on the connection of volatile components caused by heating during connection, the substrate provided with the circuit electrodes is preferably heat-treated in advance prior to the connection step using the circuit connection adhesive film.

[0098] The circuit connection structure 1 is formed, for example, by overlapping the first circuit member 20, the circuit connection adhesive film, and the second circuit member 30 in this order so that the first connection terminal 22 and the second connection terminal 32 face each other, and applying pressure or further heating in this state. The pressure is not particularly limited as long as it is within a range that does not damage the adherend, but generally 0.1 to 10 MPa is preferred. The heating temperature is not particularly limited, but 100 to 200°C is preferred. The pressure and heating are preferably carried out for a period of 0.5 to 100 seconds, and adhesion is also possible with heating at 130 to 180°C, 3 MPa, and 10 seconds. EXAMPLES

[0099] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0100] <Synthesis of polyurethane resin (PU1)> In a separable flask equipped with a reflux condenser, a thermometer, and a stirrer, 1000 parts by mass of polypropylene glycol (number average molecular weight: 2000) which is a diol having an ether bond and 4000 parts by mass of methyl ethyl ketone as a solvent were added, and the mixture was stirred at 40°C for 30 minutes. After the temperature of this solution was raised to 70°C, 0.127 parts by mass of dimethyltin laurate as a catalyst was added. Next, a solution prepared by dissolving 125 parts by mass of 4,4'-diphenylmethane diisocyanate in 125 parts by mass of methyl ethyl ketone was dropped into this solution over 1 hour. Thereafter, stirring was continued at 70°C until the absorption peak derived from the NCO group was no longer observed with an infrared spectrophotometer, and a methyl ethyl ketone solution of polyurethane resin (PU1) was obtained. Then, the amount of methyl ethyl ketone was adjusted so that the solid content concentration of this solution (concentration of polyurethane resin) was 30% by mass. The weight average molecular weight of the polyurethane resin (PU1) was 50,000. The weight average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150SG2000Hhr manufactured by Resonac Corporation Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94×10 6 Pa(30kgf / cm 2 ) Flow rate: 1.00mL / min

[0101] <Synthesis of polyurethane acrylate (UA1)> Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser having a calcium chloride drying tube, and a nitrogen gas inlet tube, 2500 parts by mass (2.50 mol) of poly(1,6-hexanediol carbonate) (trade name: Duranol T5652, manufactured by Asahi Kasei Chemicals Corporation, number average molecular weight 1000) and 666 parts by mass (3.00 mol) of isophorone diisocyanate (manufactured by Sigma-Aldrich Co.) were uniformly dropped over 3 hours. Next, after sufficient nitrogen gas was introduced into the reaction vessel, the inside of the reaction vessel was heated to 70 to 75°C to cause a reaction. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (Sigma-Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (Sigma-Aldrich) were added to the reaction vessel, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (Sigma-Aldrich) were added and reacted at 70°C for 6 hours in an air atmosphere. This resulted in polyurethane acrylate (UA1). The weight-average molecular weight of polyurethane acrylate (UA1) was 15,000. The weight-average molecular weight was measured in the same manner as the weight-average molecular weight of the polyurethane resin described above.

[0102] <Preparation of conductive particles> A layer of nickel was formed on the surface of polystyrene particles to a thickness of 0.2 μm, thereby obtaining conductive particles with an average particle size of 4 μm, a maximum particle size of 4.5 μm, and a specific gravity of 2.5. (Examples 1 to 3, Comparative Examples 1 to 4) [Preparation of adhesive film] The components shown below were mixed in the amounts (parts by mass) shown in Table 1 to prepare respective varnish compositions.

[0103] (thermoplastic resin) A1: Polyurethane resin (PU1) synthesized as described above A2: A 40% by mass solution prepared by dissolving 40 g of bisphenol A phenoxy resin (product name: PKHC, manufactured by Union Carbide) in 60 g of methyl ethyl ketone was used (the blending amount in the table indicates the blending amount of bisphenol A phenoxy resin).

[0104] (Radical polymerizable compound) B1: Polyurethane acrylate (UA1) synthesized as described above B2: Isocyanuric acid EO modified diacrylate (product name: M-215, manufactured by Toagosei Co., Ltd.) B3: Diacrylate having a tricyclodecane skeleton (dicyclopentadiene type diacrylate) (product name: DCP-A, manufactured by Kyoeisha Chemical Co., Ltd.) B4: 2-Methacryloyloxyethyl acid phosphate (product name: Light Ester P-2M, manufactured by Kyoeisha Chemical Co., Ltd.)

[0105] (Radical polymerization initiator) C1: Benzoyl peroxide (product name: Niper BMT-K40, manufactured by NOF Corporation) C2: Lauroyl peroxide (product name: Perloyl L, manufactured by NOF Corporation)

[0106] (Coupling Agent) E1: 3-methacryloxypropyltrimethoxysilane (product name: KBM503, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0107] (Non-conductive filler) F1: Spherical glass filler ("DL7400" (manufactured by Nippon Electric Glass Co., Ltd., product name, linear thermal expansion coefficient (average value from 30 to 150°C): -1.1 ppm / °C, average particle size (primary particle size): 2 μm) F2: Silica fine particles (product name: R104, manufactured by Nippon Aerosil Co., Ltd., average particle size (primary particle size): 12 nm)

[0108] (Conductive particles) G1: Conductive particles prepared as described above

[0109] The varnish composition obtained above was applied onto a PET film having a thickness of 50 μm using a coating device, and then hot air drying was performed at 70° C. for 3 minutes to form an adhesive film having a thickness (thickness after drying) of 10 μm on the PET film.

[0110] [Reaction rate of adhesive film when heated at 180°C for 1 minute] The reaction rate of the adhesive film when heated at 180° C. for 1 minute was determined by the following procedure. (Response rate) Two pre-heated samples each containing 5 mg of the adhesive composition were prepared. Next, one pre-heated sample was heated in an air atmosphere (atmosphere) at 180°C for 1 minute to obtain a post-heated sample. The pre-heated sample and the post-heated sample were each measured for DSC heat generation in a nitrogen gas flow at a measurement temperature range of 30°C to 250°C and a heating rate of 10°C / min using a differential scanning calorimeter (DSC7, manufactured by PERKIN ELMER). Based on the measured DSC heat generation, the reaction rate when heated at 180°C for 1 minute was calculated using the following formula. Reaction rate = (Cx-Cy) x 100 / Cx [In the formula, Cx represents the DSC calorific value (J / g) of the sample before heating, and Cy represents the DSC calorific value (J / g) of the sample after heating.]

[0111] The adhesive films of Examples 1 to 3 and Comparative Examples 1 to 4 had the above reaction rate of 90% or more.

[0112] [Fabrication of circuit connection structure] A 25 μm pitch COF (manufactured by FLEXSEED) and a glass substrate with thin-film electrodes (manufactured by Geomatec) with thin-film electrodes (height: 1200 Å) made of silicon nitride (SiNx) on a glass substrate were connected via the adhesive film prepared by heating and pressurizing at 180°C, 4.5 MPa for 4 seconds using a thermocompression bonding device (heating method: constant heat type, manufactured by Taiyo Kikai Seisakusho Co., Ltd.) over a width of 1 mm to produce a circuit connection structure (connection structure).

[0113] [Evaluation of circuit connection structures] The resulting circuit connection structure was evaluated as follows.

[0114] (Connection resistance) The connection resistance between the opposing electrodes of the obtained circuit connection structure was measured with a multimeter immediately after connection and after a high-temperature, high-humidity test. The high-temperature, high-humidity test was performed by leaving the structure in a constant temperature and humidity chamber at 85°C and 85% RH for 100 hours. The connection resistance was calculated as the average value of 16 resistance points between the opposing electrodes.

[0115] (peeling) The appearance of the connection of the connection structure prepared as described above was observed using an optical microscope immediately after connection and after a high temperature and humidity test in which the structure was left in a thermo-hygrostat at 110°C and 85% RH for 100 hours. The area of ​​peeling occurring at the substrate-resin interface in the space portion (the portion between the electrode terminals of the FPC) was measured and evaluated according to the following criteria. [Judgment criteria] A: The ratio of the peeling area to the total area of ​​the space is 10% or less B: The ratio of the peeled area to the total area of ​​the space is more than 10% and 20% or less. C: The ratio of the peeled area to the total area of ​​the space is more than 20% and less than 30%. D: The ratio of the peeled area to the total area of ​​the space is more than 30% and less than 40%. E: The ratio of the peeled area to the total area of ​​the space is more than 40%.

[0116] [Table 1]

[0117] As shown in Table 1, the adhesive films of Examples 1 to 3, which contain a non-conductive filler having an average linear thermal expansion coefficient of 0 ppb / °C or less between 30°C and 150°C, can reduce peeling that occurs in the connection structure after high temperature and high humidity testing, and can provide a circuit connection structure with excellent high temperature and high humidity connection reliability. [Explanation of symbols]

[0118] 1...circuit connection structure, 7...conductive particles, 10...connection portion, 11...insulating layer, 20...first circuit member, 21...first circuit board, 22...first circuit electrode (first connection terminal), 30...second circuit member, 31...second circuit board, 32...second circuit electrode (second connection terminal).

Claims

1. The composition comprises a thermosetting component, conductive particles, and a non-conductive filler, The adhesive composition, wherein the non-conductive filler comprises a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less between 30°C and 150°C.

2. 2. The adhesive composition according to claim 1, wherein the content of the non-conductive filler MF is 0.1 to 50 mass % based on the total mass of the adhesive composition excluding the conductive particles and the non-conductive filler.

3. The adhesive composition according to claim 1 , comprising, as the thermosetting component, a radically polymerizable compound and a radical polymerization initiator.

4. The adhesive composition of claim 1 further comprising a thermoplastic resin.

5. 2. The adhesive composition according to claim 1, which has a reaction rate of 90% or more when heated at 180°C for 1 minute.

6. The adhesive comprises a thermoplastic resin, a thermosetting component, conductive particles, and a non-conductive filler, The adhesive film for circuit connection, wherein the non-conductive filler comprises a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less between 30°C and 150°C.

7. 7. The adhesive film for circuit connection according to claim 6, wherein the content of the non-conductive filler MF is 0.1 to 50 mass % based on the total mass of the adhesive film excluding the conductive particles and the non-conductive filler.

8. 7. The adhesive film for circuit connection according to claim 6, comprising a radical polymerizable compound and a radical polymerization initiator as the thermosetting component.

9. 7. The adhesive film for circuit connection according to claim 6, which has a reaction rate of 90% or more when heated at 180°C for 1 minute.

10. a first circuit member having a first electrode; a second circuit member having a second electrode; a connection portion disposed between the first circuit member and the second circuit member, the connection portion electrically connecting the first electrode and the second electrode to each other; A circuit connection structure, wherein the connection portion includes conductive particles and a non-conductive filler MF having an average linear thermal expansion coefficient of 0 ppb / °C or less between 30°C and 150°C.

11. The circuit connection structure according to claim 10, wherein the connection portion comprises a cured product of the adhesive composition according to any one of claims 1 to 5.

12. a first circuit member having a first electrode; a second circuit member having a second electrode; An adhesive film for circuit connection according to any one of claims 6 to 8, A method for manufacturing a circuit connection structure, comprising a step of applying heat and pressure to the first electrode and the second electrode while the first electrode and the second electrode are arranged so as to face each other via the adhesive film for circuit connection, thereby electrically connecting the first electrode and the second electrode.

Citation Information

Patent Citations

  • Thermosetting anisotropically electroconductive adhesive

    JP1989113480A

  • Circuit connecting material, method for manufacturing circuit board using it, and circuit board

    JP2002203427A

  • Circuit connecting material, and structure and method of connecting circuit terminal

    WO1998044067A1